The inviolability of medical confidentiality:an analysis of the rules and exceptions - Jahn Kassim, Puteri Nemie; Ramli, Nazri (2016)
The duty of medical confidentiality has been one of the core duties of medical practice as information created, disclosed, acquired directly or indirectly during the doctor-patient relationship is considered confidential and requires legitimate protection. Further, preserving confidentiality on the premise that the relationship between doctor and patient has been built on trust and confidence renders the duty to be seen as sacrosanct. The source for this duty can be found not only in the Hippocratic Oath, codes of ethics, religious tenets but also in the common law, principles of equity and statutory provisions. Nevertheless, technological advancements and the growth of social networks have contributed to the difficulties in preserving confidentiality as the information gathered tends to become vulnerable in unsecure environments. However, the duty of medical confidentiality is by no means absolute as it can be breached in situations in which there are stronger conflicting duties. This paper seeks to discuss the rules governing the duty of medical confidentiality and the exceptions in which infringements to this duty become justified. The scope and limitations of this duty under the Islamic law will also be discussed as infringements on confidentiality make up a significant portion of Islamic rulings that should be thoroughly explored and investigated to understand the demands of this duty on Muslim medical practitioners. The inviolability of this duty may be without doubt but circumstances warranting its disclosure are crucial to serve the interests of justice.